Biometeorological Assessment of Mortality Related to Extreme Temperatures in Helsinki Region, Finland, 1972–2014 - Ruuhela, Reija (Int J Environ Res Public Health, 2017)
Climate change is expected to increase heat-related and decrease cold-related mortality. The extent of acclimatization of the population to gradually-changing thermal conditions is not well understood. We aimed to define the relationship between mortality and temperature extremes in different age groups in the Helsinki-Uusimaa hospital district in Southern Finland, and changes in sensitivity of the population to temperature extremes over the period of 1972–2014. Time series of mortality were made stationary with a method that utilizes 365-day Gaussian smoothing, removes trends and seasonality, and gives relative mortality as the result. We used generalized additive models to examine the association of relative mortality to physiologically equivalent temperature (PET) and to air temperature in the 43-year study period and in two 21-year long sub-periods (1972–1992 and 1994–2014). We calculated the mean values of relative mortality in percentile-based categories of thermal indices. Relative mortality increases more in the hot than in the cold tail of the thermal distribution. The increase is strongest among those aged 75 years and older, but is somewhat elevated even among those younger than 65 years. Above the 99th percentile of the PET distribution, the all-aged relative mortality decreased in time from 18.3 to 8.6%. Among those ≥75 years old, the decrease in relative mortality between the sub-periods were found to be above the 90th percentile. The dependence of relative mortality on cold extremes was negligible, except among those ≥75 years old, in the latter period. Thus, heat-related mortality is also remarkable in Finland, but the sensitivity to heat stress has decreased over the decades.